The Place of Generative Artificial Intelligence in Digital Security Studies - Ay, Sevinç; Karakuş, Songül (My University, 2025)
Digital security has become critically important today as cyber threats continue to diversify. This study aims to systematically examine the place of generative artificial intelligence in the digital security literature. In this context, documents obtained from a search using the keywords generative artificial intelligence and cybersecurity or information security have been compiled from the Web of Science (WoS) and Scopus databases as of September 3, 2025. As a result of the compilation, 37 duplicate documents were removed, and the remaining 350 papers were analyzed using RStudio, VOSviewer, and Gephi. The research covers themes such as the distribution of academic studies by year, author productivity, collaboration networks, country, institution, resource allocation, keywords, and topics covered. The findings reveal that research in the field increased particularly between 2024 and 2025. According to Lotka's law, author productivity indicates that most authors contribute with a single publication, while a small number of productive authors have played a central role in the development of the field. The keyword analysis demonstrates that generative AI research is developing in two directions, both in the context of health/data privacy and cybersecurity/threat analysis. Finally, a country-by-country analysis reveals that the USA and India are the leading countries contributing most to the field, while the rate of international collaboration is low. In conclusion, this study demonstrates that generative AI is an important interdisciplinary research theme in digital security and is expected to guide future studies.
Keywords: Information security; Cyber security; Bibliometric analysis; Digital security; Generative artificial intelligence